1998
DOI: 10.2527/1998.7692405x
|View full text |Cite
|
Sign up to set email alerts
|

Pork carcass composition: II. Use of indicator cuts for predicting carcass composition.

Abstract: Right sides of 30 pork carcasses were fabricated into indicator cuts (Boston butt, picnic, anterior belly, posterior belly, anterior loin, posterior loin, and ham) and used to determine carcass composition by physical dissection and chemical analysis of soft tissue. Linear measures and chemical composition of whole-side grind were collected from left sides. Dissection of indicator cuts to predict dissectable composition of the side were much better indicators than linear measures ( R 2 = .70 to .94). Chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, studies have consistently shown that dissection of any primal cut is a more accurate estimate of carcass lean content than any linear carcass measure. Swensen et al ( 1998) found the loin to be the most accurate estimator of both dissectable lean and fatfree lean (R 2 = 0.90 and 0.89).…”
Section: Linear Carcass Measuresmentioning
confidence: 94%
See 1 more Smart Citation
“…However, studies have consistently shown that dissection of any primal cut is a more accurate estimate of carcass lean content than any linear carcass measure. Swensen et al ( 1998) found the loin to be the most accurate estimator of both dissectable lean and fatfree lean (R 2 = 0.90 and 0.89).…”
Section: Linear Carcass Measuresmentioning
confidence: 94%
“…Other more efficient and less costly measures needed to be found. Sample joint dissection has been revisited several times but has still been found to be too expensive, laborious, and destructive (Swensen et al, 1998;Planella and Cook, 1991;Kempster and Evans, 1981;Evans and Kempster, 1979;Cuthbertson et al, 1968;Adam and Smith, 1966). However, studies have consistently shown that dissection of any primal cut is a more accurate estimate of carcass lean content than any linear carcass measure.…”
Section: Linear Carcass Measuresmentioning
confidence: 99%
“…A 10 g sample of soft tissue was oven-dried at 110 °C for approximately 24 h to determine percentage moisture. The dried sample was then washed multiple times in an azeotropic mixture of warm chloroform/methanol, as described by Swensen et al [ 22 ], to determine the fat content of the soft tissue. Finally, the percentage of carcass weight, categorized as fat vs. fat-free lean, was calculated for each pig.…”
Section: Methodsmentioning
confidence: 99%
“…Adipose tissue is an important component accounting for a considerable ratio in a pig carcass (Mas et al., 2011; Swensen et al., 1998). In recent past decades, the pig breeding programs for improving protein deposition and the genetic selection for increased growth rate have resulted in limited amount of visible fat in body and meat tissues as well as decreased back‐fat (BF) thickness (Gjerlaug‐Enger et al., 2010; Hamill et al., 2012; Sonesson et al., 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue is an important component accounting for a considerable ratio in a pig carcass (Mas et al, 2011;Swensen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%